1993
DOI: 10.1111/j.1432-1033.1993.tb18106.x
|View full text |Cite
|
Sign up to set email alerts
|

Glucose administration induces the premature expression of liver glucokinase gene in newborn rats

Abstract: Glucokinase first appears in the liver of the rat 2 weeks after birth and its activity rapidly increases after weaning on to a high-carbohydrate diet. The appearance of glucokinase is principally due to the increase of plasma insulin and to the decrease of plasma glucagon concentrations. Oral glucose administration to 1-or 10-day-old suckling rats induced an increase in plasma insulin and a fall in plasma glucagon and allowed a rapid accumulation of liver glucokinase mRNA, secondarily to a stimulation of gene … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
25
1

Year Published

1994
1994
2008
2008

Publication Types

Select...
4
2

Relationship

2
4

Authors

Journals

citations
Cited by 21 publications
(27 citation statements)
references
References 45 publications
1
25
1
Order By: Relevance
“…To answer this question, two types of experiments were performed. First, as previously reported, the oral administration of glucose to 10-day-old suckling rats provoked a rapid accumulation (within 6 h) of glucokinase mRNA by increasing the rate of gene transcription [38]. After 18 h, both glucokinase mRNA and gene transcription had returned to very low values [38].…”
Section: Exposure Of Suckling Rat Liver To High Plasma Insulin Level mentioning
confidence: 54%
“…To answer this question, two types of experiments were performed. First, as previously reported, the oral administration of glucose to 10-day-old suckling rats provoked a rapid accumulation (within 6 h) of glucokinase mRNA by increasing the rate of gene transcription [38]. After 18 h, both glucokinase mRNA and gene transcription had returned to very low values [38].…”
Section: Exposure Of Suckling Rat Liver To High Plasma Insulin Level mentioning
confidence: 54%
“…The Gck promoter structure [13,28,38], shown in Fig. 2a by nest PCR from nt −518 to nt +83 and sequenced directly.…”
Section: Resultsmentioning
confidence: 99%
“…Here, we have presented data to support the notion that differential DNA methylation results in the agedependent reduction of Gck expression. The Gck promoter structure [13,28,38] is shown in Fig. 2a.…”
Section: Discussionmentioning
confidence: 99%
“…This fragment is located at the beginning of the first intron of the gene. The probe was labelled by random priming and the blot was washed as described [9] before autoradiography.…”
Section: Dnase Hypersensitives Sitesmentioning
confidence: 99%
“…Indeed mutasensitive sites (Hss), which are indicative of nucleosome disruption. This technique has shown that, both in rats and in mice, the hepatic promoter of the glucokinase gene encompasses about 7 kb of 5′ flanking sequence [9,10,11]. The factors that determine the liver-specific transcription of the hepatic glucokinase mRNA have not been identified.…”
mentioning
confidence: 99%